Displacement measurement of soft material indentation using light intensity / Mohd Nadzeri Omar and Mohd Hasnun Arif Hassan - Omar, Mohd Nadzeri; Hassan, Mohd Hasnun Arif (Universiti Teknologi MARA, 2022)
This paper studies proof of concept in which soft material displacement during indentation is measured by a change in light intensity as the indenter is pushed into a soft material. The Light Dependent Resistor (LDR) sensor, which is embedded within a transparent hemispheric indenter, is used to measure the intensity of light while the indenter is on the surface and within the soft material. The change in light intensity contributes to a gradient that can be used to calculate the displacement of the soft material. The calculated difference in light intensity is converted into a displacement with the mean conversion factor obtained from the calibration equation. Measurements were carried out on three silicone samples with varying elastic properties over a range of different light intensities. By referring to linear regression and R-squared values, the proposed concept has high consistency in measuring the difference of light intensity for various materials at different initial light intensities with more than 95% of R-squared values. In addition, the mean of variance between measurements, reflecting repeatability, is within an outstanding 1.5%. In the meantime, the accuracy of the proposed concept tested concerning the actual displacement is less than 10% of the variation. With promising results, the proposed design can be applied as a standalone technology or as an extension to a hand-held soft material characterization device for further improvement.